PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN ANIMASI TERHADAP HASIL BELAJAR IPS PADA SISWA KELAS IV SDN BOJONG 1 - Rojana, Salsa; Arry Patriasurya Azhar; Ino Budiatman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The aim of this research is to find out the impact of the use of animation learning media on the learning outcomes of IPS class IV SDN Bojong 1. The method used in this research is a quasi-experimental method with a design of nonequivalent control group design. The research was carried out at SDN Bojong 1 with sampling techniques using saturated samplings. In this study, class IV-A as an experimental class used an animated learning medium, while class IV-B as a control class did not use an animation learning medium. The data collection technique uses a test on the essay, and the data analysis technique uses the test-t. The calculation of the hypothetical test using the test -t on the posttest data shows that the thitung is 3.67 > a table of 2.01. Then, Ho was rejected and Ha accepted. Study results show that students' learning outcomes using animated learning media have improved significantly. Thus, it can be concluded that there is an influence of the use of animation learning media on the learning outcomes of IPS in the students of the fourth grade of SDN Bojong 1 City of Tangerang.